Student Perception of Teacher and Parent Involvement in Homework and Student Engagement: The Mediating Role of Motivation - Núñez, José C.; Regueiro, Bibiana; Suárez, Natalia; Piñeiro, Isabel; Rodicio, María Luisa; Valle, Antonio (Frontiers in Psychology, 2019)
Currently, the appropriateness of assigning homework is under debate. Official organizations like the OECD conclude that doing more homework is not synonymous with higher performance. Current research suggests that this is mainly a consequence both of the way of assigning homework and the type of student engagement when doing it. In this sense, the relationship between homework and academic achievement is positive and more intense when homework is carried out from a deep, or comprehensive, approach. This study was intended to investigate the role of the parental and teacher involvement as precursors of the type of student homework engagement. Seven hundred and thirty students of Compulsory Secondary Education, (7th to 10th grade), from 14 schools in the north of Spain participated. A structural equations model was adjusted which examined extent to which: (a) parental involvement (e.g., supportive behavior) and the teacher involvement (e.g., adjusting homework to the particular needs of the students, and subsequent feedback) determines the students’ motivation (e.g., interest to master and understand); and (b) this conditions students’ the cognitive work on the tasks (e.g., use of cognitive strategies for understanding and elaboration). The results obtained suggest that the greater or lesser use of significant cognitive strategies is closely linked to student's type of motivation, and this, in turn, to the type of teacher involvement (mainly), and of parental involvement (to a lesser extent).